User manual formapping Member State avian influenzastandard terminologyto EFSA standard terminology. Issue 10 (28th October 2019) - ,; Aznar, Inma; Mulligan, Kenneth; Stoicescu, Anca‐Violeta
Abstract : Avian influenza surveillance data should be submitted from Member States to the European Food Safety Authority (EFSA) using the EFSA Standard Sample Description version 2 (SSD2). For data transmission purposes, EFSA created aMicrosoft OfficeExcel‐based mapping tool to allow Member States (MSs) to map their standard terminology to EFSA's standard terminology. This technical report is a user manual for data providers, describing how MSs terms can be mapped, and how to generate extensible markup language (XML) for submission of 2019data to EFSAaccording tothe avian influenzadata model.